MOTHERS' BELIEFS IN EARLY CHILDHOOD CARE AND DEVELOPMENT - Yunia Indarwati; Lilis Madyawati; Indiati Indiati (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2023)
The mother's confidence in the care and development of early childhood is very important because it will influence the child's parenting patterns. Therefore, knowing mothers' beliefs in parenting and early childhood development is the aim of this research. Mothers' confidence in implementing care for children has a big impact on optimizing aspects of children's development. The survey was conducted involving 45 mothers. The instrument used is the Early Parenting Attitude Questionnaire (EPAQ). Descriptive statistical analysis and Eta test as analysis techniques in this research. The findings obtained show that 1) the initial learning (EL) aspect has a low average, especially in the statement that providing an explanation about the reasons for the enactment of regulations will not be effective because children do not understand and children do not need to learn about numbers and mathematics until children enter school, and 2) there is a large relationship in parenting beliefs with educational background as well as maternal employment. The findings obtained were that the majority of mothers had positive beliefs in caring for children, but parenting seen from initial learning activities at home was still lacking. The implication of this study is that by creating a program, one of which is that mother schools can provide opportunities for prospective mothers or mothers to learn about parenting. Apart from that, mothers also need to be equipped with self-management of emotions so that mothers can manage their emotions when caring for their children.